Keys to leading highly effective data science teams (Data Science Salon, 2019)
"Presented by Darby Laffoon, Sr Manager, Big Data Platform Engineering at Charles Schwab. In this session, we will walk through the various aspects of how to build and manage effective data science teams, and how to navigate the many challenges that come with such an undertaking. While there is no right or wrong, experience tells us that there are a multitude of ways to approach any challenge therein, and that's where we will focus much of our energy."--Resource description page